Publicising chemistry in a multicultural society through chemistry outreach - Harrison, Timothy; Shallcross, Dudley; Norman, Nicholas; Sewry, Joyce; Davies-Coleman, Michael (South African Journal of Science, 2011)
Given the emphasis in Higher Education on community engagement in South Africa and the importance of international collaboration, we discuss a joint approach to chemistry outreach in two countries on two continents with widely differing target school audiences. We describe the history of the partnership between the chemistry departments at Rhodes University and the University of Bristol and provide an outline of the chemistry content of their outreach initiatives, the modes of delivery, the advantages to both departments and their students for involvement in various levels of outreach, the challenges they still face and additional opportunities that such work facilitated. The lecture demonstration 'A Pollutant's Tale' was presented to thousands of learners all over the world, including learners at resource-deprived schools in South Africa. Challenges to extend outreach activities in South Africa include long travelling distances, as well as a lack of facilities (such as school halls and electricity) at schools. Outreach activities not only impacted on the target audience of young learners, they also impacted upon the postgraduate and other chemistry students taking part in these initiatives. This collaboration strengthened both institutions and their outreach work and may also lead to chemistry research collaborations between the academics involved.